2020
DOI: 10.1038/s41419-020-2594-x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of soluble epoxide hydrolase attenuates renal tubular mitochondrial dysfunction and ER stress by restoring autophagic flux in diabetic nephropathy

Abstract: Diabetic nephropathy (DN) is the leading cause of end-stage renal disease (ESRD), and renal tubular cell dysfunction contributes to the pathogenesis of DN. Soluble epoxide hydrolase (sEH) is an enzyme that can hydrolyze epoxyeicosatrienoic acids (EETs) and other epoxy fatty acids (EpFAs) into the less biologically active metabolites. Inhibition of sEH has multiple beneficial effects on renal function, however, the exact role of sEH in hyperglycemiainduced dysfunction of tubular cells is still not fully elucida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 56 publications
1
34
0
Order By: Relevance
“…For instance, Luo et al demonstrated in rat models of DKD that hyperglycemia decreases EETs production in the glomeruli, changes that may be important in causing glomerular damage in the early stage of DKD (Luo et al, 2009[ 25 ]). Moreover, an enhanced sEH expression (resulting in low levels of EETs) in murine kidneys under streptozotocin-induced diabetes (Chen et al, 2012[ 3 ]; Bettaieb et al, 2017[ 2 ]; Jiang et al, 2020[ 23 ]) and in cells exposed to hyperglycemia (Jiang et al, 2020[ 23 ]) has been repeatedly observed. Indeed, an elevation of EETs levels by inhibition of sEH have been suggested as a potential therapeutic strategy for the amelioration of DKD (Chen et al, 2012[ 3 ], Jiang et al, 2020[ 23 ]).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For instance, Luo et al demonstrated in rat models of DKD that hyperglycemia decreases EETs production in the glomeruli, changes that may be important in causing glomerular damage in the early stage of DKD (Luo et al, 2009[ 25 ]). Moreover, an enhanced sEH expression (resulting in low levels of EETs) in murine kidneys under streptozotocin-induced diabetes (Chen et al, 2012[ 3 ]; Bettaieb et al, 2017[ 2 ]; Jiang et al, 2020[ 23 ]) and in cells exposed to hyperglycemia (Jiang et al, 2020[ 23 ]) has been repeatedly observed. Indeed, an elevation of EETs levels by inhibition of sEH have been suggested as a potential therapeutic strategy for the amelioration of DKD (Chen et al, 2012[ 3 ], Jiang et al, 2020[ 23 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an enhanced sEH expression (resulting in low levels of EETs) in murine kidneys under streptozotocin-induced diabetes (Chen et al, 2012[ 3 ]; Bettaieb et al, 2017[ 2 ]; Jiang et al, 2020[ 23 ]) and in cells exposed to hyperglycemia (Jiang et al, 2020[ 23 ]) has been repeatedly observed. Indeed, an elevation of EETs levels by inhibition of sEH have been suggested as a potential therapeutic strategy for the amelioration of DKD (Chen et al, 2012[ 3 ], Jiang et al, 2020[ 23 ]). According to these preclinical data, an sEH inhibition leads to higher concentrations of EETs which, in turn, attenuate renal tubular mitochondrial dysfunction and endoplasmic reticulum stress by restoring autophagic flux, as well as decreasing renal tubular apoptosis (Chen et al, 2012[ 3 ]; Jiang et al, 2020[ 23 ]).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies showed sEH is a physiological modulator of ER stress signaling involved in many disorders. [105][106][107] Thus, the sEH enzyme is a nonchannel, non-neurotransmitter therapeutic and well characterized target for pain. 108 Both pain and ER stress markers are elevated in peripheral nervous system of type I diabetic rats.…”
Section: Endoplasmic Reticulum (Er) Stress Signaling Pathway In Painmentioning
confidence: 99%